Dignity, the Voice of Elder Care: Concept Analysis - Esmaeili, Roghayeh; Esmaeili, Mehrdad; Kiani, Zahra (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: The current study aimed at analyzing the concept of dignity for elderly population in Iran to provide a more accurate definition and perception of this notion. The study used a hybrid model of concept analysis, while systematic review of literature aimed at providing working definitions in the research theoretical stage. Methods: A hybrid model of concept analysis was conducted. Definitions Dignity care for the elderly were obtained from a systematic literature review in the theoretical phase. This systematic review was conducted without any time limitation in international databases such as Pro Quest, SCOPUS, MEDLINE, Web of Sciences and Iranmedex using relevant keywords by 2 reviewers separately. Subsequent in-depth personal interviews initiated in the fieldwork phase corroborated and refined the concept. Interviews with the fifteen elder took place during December 2014 to January 2015 in Tehran. These qualitative data were integrated in the final analytical phase. Results: The older people’s dignity can be considered a complicated and dynamic mental condition leading to the improvement of internal feelings. Personal, family, as well as social components affect dignity whose formation depends on relations with other people, ensuring the individual health. Elders’ dignity can be practically defined in association with the domains of dignity in older people, reflecting relative dignity that stems in cultural values and undergoes changes. Elders’ dignity can be characterized by respect, integrity, independence and authority, privacy, unique support as well as engagement in the self-care. The predisposing factors as well as antecedents are dependent on the individual, family, and social dimensions to establish such features. Conclusions: Explicit conceptualization of dignity in the context of healthcare services results in a better perception of this notion among practitioners, while also improving the contribution of moral factors to the service delivery.